Primary coenzyme Q deficiency in Pdss2 mutant mice causes isolated renal disease. - Min Peng; Marni J Falk; Volker H Haase; Rhonda King; Erzsebet Polyak; Mary Selak; Marc Yudkoff; Wayne W Hancock; Ray Meade; Ryoichi Saiki; Adam L Lunceford; Catherine F Clarke; et al. (PLoS Genetics)
Coenzyme Q (CoQ) is an essential electron carrier in the respiratory chain whose deficiency has been implicated in a wide variety of human mitochondrial disease manifestations. Its multi-step biosynthesis involves production of polyisoprenoid diphosphate in a reaction that requires the enzymes be encoded by PDSS1 and PDSS2. Homozygous mutations in either of these genes, in humans, lead to severe neuromuscular disease, with nephrotic syndrome seen in PDSS2 deficiency. We now show that a presumed autoimmune kidney disease in mice with the missense Pdss2(kd/kd) genotype can be attributed to a mitochondrial CoQ biosynthetic defect. Levels of CoQ9 and CoQ10 in kidney homogenates from B6.Pdss2(kd/kd) mutants were significantly lower than those in B6 control mice. Disease manifestations originate specifically in glomerular podocytes, as renal disease is seen in Podocin/cre,Pdss2(loxP/loxP) knockout mice but not in conditional knockouts targeted to renal tubular epithelium, monocytes, or hepatocytes. Liver-conditional B6.Alb/cre,Pdss2(loxP/loxP) knockout mice have no overt disease despite demonstration that their livers have undetectable CoQ9 levels, impaired respiratory capacity, and significantly altered intermediary metabolism as evidenced by transcriptional profiling and amino acid quantitation. These data suggest that disease manifestations of CoQ deficiency relate to tissue-specific respiratory capacity thresholds, with glomerular podocytes displaying the greatest sensitivity to Pdss2 impairment.